Top story eaudiobook - Yang, Kelly (Front Desk, 2023)
The New York Times bestselling Front Desk series continues! Mia Tang is at the top of her game! She's spending winter break with Mom, Lupe, Jason, and Hank in San Francisco's Chinatown! Rich with history and hilarious aunties and uncles, it's the place to find a great story-one she hopes to publish while attending journalism camp at the Tribune. But this trip has as many bumps as the hills of San Francisco . . . 1. Mia's camp is full of older kids, with famous relatives, fancy laptops, and major connections! Can she compete with just her pen and passion? 2. Lupe's thinking about skipping ahead to college! Will Mia ever get a chance to just chill with her best friend? 3. Jason's crushing hard on a new girl. For the first time ever, Mia is speechless...and jealous. Can she find the courage to tell Jason-gulp-that she has a crush on him? Even for the best writers, it's not always easy to find the right words. But if anyone can tell a top story, it's Mia Tang!